Vaccinal Prevention of the Diseases Caused by Human Papillomavirus: Evidence-Based Medicine. Review of Clinical Guidelines - Alexander A. Baranov; Leyla S. Namazova-Baranova; Vladimir K. Tatochenko; Elena A. Vishneva; Marina V. Fedoseenko; Liliia R. Selimzianova; Dariya S. Chemakina; Yuriy V. Lobzin; Susanna M. Kharit; Nikolay I. Briko; Platon D. Lopukhov; Gennadiy T. Sukhikh; et al. ("Paediatrician" Publishers LLC, 2017)
The article is devoted to the urgent problem of papillomavirus infection, the extremely high prevalence of which determines the key contribution to the structure of morbidity and mortality from oncological diseases. A chronic persistent course, resulting in benign and malignant tumors in the infection atrium, makes scientists seek new ways of treatment. A specific vaccinal prevention is recognized to be the only reliable protection method today. The article is an updated review of the clinical guidelines developed and approved by the professional association «Union of Pediatricians of Russia» in 2016 for a vaccinal prevention of the diseases caused by human papillomavirus, first published on pediatr-russia.ru. The widespread introduction of vaccines against human papillomavirus, which have confirmed the clinical efficacy and safety, can significantly reduce the global burden of diseases associated with papillomavirus infection.